Improving the Scientific Attitude of Elementary School Students Through Problem-Based Learning - Wibawa, I Made Citra; Susanta, I Wayan; Parmithi, Ni Nyoman; Mahendra, I Wayan Eka (Universitas Pendidikan Ganesha, 2023)
Learning science at the elementary school level still faces various obstacles. These obstacles are caused by low interest and motivation in learning, activities in learning that are still monotonous or conventional, and other constraints. This study aims to investigate the effect of problem-based learning (PBL) approach on students' scientific attitudes in elementary school. This study used an experimental research design with a randomized control group. The population of this study was grade V students. The research sample consisted of 38 students who were divided into two groups, namely the experimental group and the control group. Data was collected through several methods, namely daily test scores and student scientific attitude questionnaires. Data analysis is carried out using appropriate statistical tests. To compare the difference in student achievement between the experimental group and the control group, the average daily test scores before and after the treatment were compared. Meanwhile, differences in scientific attitudes between the two groups were analyzed using the one-track ANOVA test after confirming the normality of data distribution and homogeneity of variants between groups. The results showed that students who followed the PBL approach obtained higher scores than those who followed the conventional approach in terms of scientific attitudes. The implication of this research is to contribute to the development of science learning in elementary schools with a focus on developing students' scientific attitudes, motivation, creativity, and critical thinking.